1999
DOI: 10.3109/08923979909052768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lansoprazole on Human Leukocyte Function

Abstract: Recent findings on the capacity of omeprazole to influence various leukocyte functions, in vitro, raises the question on the potential use of protonic pump inhibitors, commonly used in the treatment of acid-secretion-related disorders, as immunomodulators. The aim of this study was to evaluate the in vitro effect of lansoprazole on human natural killer (NK) cell cytotoxix activity, chemotaxis and superoxide anion (O2*-) generation exerted by polymorphonucleated cells (PMNs). NK cytotoxicity activity was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…10 This may, in turn, predispose to microaspiration of bacterial gastrointestinal contents and pneumonia. Furthermore, evidence shows that proton pump inhibitors impair immune cell function, [31][32][33][34] which is another potential mechanism to explain the differential risk that we observed.…”
Section: Possible Explanations and Implicationsmentioning
confidence: 78%
“…10 This may, in turn, predispose to microaspiration of bacterial gastrointestinal contents and pneumonia. Furthermore, evidence shows that proton pump inhibitors impair immune cell function, [31][32][33][34] which is another potential mechanism to explain the differential risk that we observed.…”
Section: Possible Explanations and Implicationsmentioning
confidence: 78%
“…52 Third, in vitro studies have shown that acid-suppressive drugs may impair the function of neutrophils and the activity of natural killer cells. [53][54][55][56][57][58][59] Interestingly, the most striking increase in the risk of pneumonia in association with proton pump inhibitors was observed in the first week of use. The risk of pneumonia in association with use of proton pump inhibitors was attenuated, but still significant, between 30 and 180 days.…”
Section: Main Findingsmentioning
confidence: 99%
“…The Gulmez study [45] also identified a temporal relationship between PPI treatment and pneumonia. The highest incidence of pneumonia was associated with PPI administration within seven days of diagnosis, with an odds ratio of 5.0 (95% CI: 2.1-11.7).…”
Section: Pneumonia: Literature Reviewmentioning
confidence: 99%
“…The humoral defense mechanism against bacterial colonization is mediated by the white blood cells. In vitro studies [43][44][45] have assessed the cytotoxicity of natural killer (NK) cells when exposed to target cells in varying ratios and in different solution media. Not surprisingly, as the ratio of NK cells to target cells increased, the percentage of target cells lysed increased, suggesting a positive correlation.…”
Section: Ppis and Pneumonia-pathophysiologymentioning
confidence: 99%